Real-world survey of pneumonitis and its impact on durvalumab consolidation therapy in patients with non-small cell lung cancer who received chemoradiotherapy after durvalumab approval (HOPE-005/CRIMSON). (November 2021) - Saito, Go; Oya, Yuko; Taniguchi, Yoshihiko; Kawachi, Hayato; Daichi, Fujimoto; Matsumoto, Hirotaka; Iwasawa, Shunichiro; Suzuki, Hidekazu; Niitsu, Takayuki; Miyauchi, Eisaku; Yokoi, Takashi; Yokoyama, Toshihide; et al.
Highlights: We retrospectively evaluated 302 patients with NSCLC who started CRT. Any grade of, symptomatic, or fatal pneumonitis occurred in 83%, 34%, and 1%. The predictive factors for symptomatic pneumonitis were V20 ≥ 25% and MLD ≥ 10 Gy. 41% of patients with pneumonitis requiring corticosteroids rechallenged durvalumab. PACIFIC rechallenge criteria were adhered to in 81%, and did not cause severe relapse. Abstract: Objectives: The incidence of real-world pneumonitis and durvalumab rechallenge during chemoradiotherapy and durvalumab consolidation for non-small cell lung cancer is unknown. Materials and methods: We retrospectively evaluated the medical records of 302 consecutive patients diagnosed with non-small cell lung cancer who started chemoradiotherapy between May 2018 and May 2019. Results: Median age was 70 (range: 40–87) years. Volume of lung parenchyma that received 20 Gy (V20) exceeded 35% in 2% and mean lung dose exceeded 20 Gy in 1% of patients. Durvalumab consolidation was delivered to 225 patients (75%). Overall, 83% (n = 251), 34% (n = 103), 7% (n = 21), and 1% (n = 4) of the patients developed any grade of pneumonitis, symptomatic pneumonitis, ≥grade 3 pneumonitis, and fatal (grade 5) pneumonitis, respectively. Corticosteroids were administered to 25% of the patients to treat pneumonitis. Multivariate analysis identified the predictive factors for the development of symptomatic pneumonitis: V20 Gy or more ≥ 25% (odds ratio [OR]: 2.37, P  = 0.008) and mean lung dose (MLD) ≥ 10 Gy (OR: 1.93, P  < 0.0047). Of the 52 patients who received corticosteroids for pneumonitis after durvalumab initiation, 21 were rechallenged with durvalumab. Overall, 81% of patients met the PACIFIC study's rechallenge criteria and did not experience a severe pneumonitis relapse. Conclusion: High V20 and MLD were independent risk factors of symptomatic pneumonitis. More than 80% of the patients who were rechallenged with durvalumab after pneumonitis met the PACIFIC study's rechallenge criteria. Consequently, severe relapse did not occur. Cooperation between radiation and medical oncologists is important for safe chemoradiotherapy and the safe completion of durvalumab consolidation therapy.